Status Items from the Crypt “Kamennaya Mogila” (Stone Grave) of the 3rd – 2nd Centuries BC (Southern Outskirts of Zheleznovodsk) - Yury Prokopenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. The article is devoted to the analysis of objects discovered during the excavation of the “Kamennaya mogila” (Stone Grave) kurgan on Medovaya mountain (southern outskirts of Zheleznovodsk). Methods and materials. The comparative typological method was used as a worker. It is based on classification by material, processing method, shape, ornamentation, as well as on the study of types of gold jewelry, glass and black-glazed dishes, bronze horse plate foreheads and cheek pads, etc. Analysis. The typological and chronological analysis was carried out on gold jewelry (plaques, rings, pendants), antique ceramic and glassware, items of horse dress and weapons. Analogies to imported items from the crypt, found in the monuments of ancient culture and in the burials of the barbarian nobility, allow them to be dated to the 4th – 2nd centuries BC. Items of equestrian dress and weapons date back to the 3rd – 2nd centuries BC. Results. The author, regarding the social structure of the local population, ranked the monument as stratum No. 2 (nobility of the first level). A complex burial structure of the tomb with a significant number of ritual offerings is recorded. Burial items have numerous analogies in the status burials of the Bosporan, Meotian and Scythian nobility of the Northern Black Sea region and the North Caucasus of the 4 th – 2nd centuries BC. The sophisticated frame structure of the horse harness made of iron parts from the crypt of the Stone Grave is unique. Only a member of the nobility with a very high status could afford such a special bridle as a ritual offering.